Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Sure, let's find the zeroes of the function [tex]\( f(x) = \sqrt{5x - 1} - 2 \)[/tex].
Step 1: Set the function equal to zero.
To find the zeroes of the function, we set [tex]\( f(x) = 0 \)[/tex]:
[tex]\[ \sqrt{5x - 1} - 2 = 0 \][/tex]
Step 2: Solve for [tex]\( \sqrt{5x - 1} \)[/tex].
[tex]\[ \sqrt{5x - 1} = 2 \][/tex]
Step 3: Square both sides to eliminate the square root.
[tex]\[ (\sqrt{5x - 1})^2 = 2^2 \][/tex]
[tex]\[ 5x - 1 = 4 \][/tex]
Step 4: Solve for [tex]\( x \)[/tex].
Add 1 to both sides:
[tex]\[ 5x = 5 \][/tex]
Divide both sides by 5:
[tex]\[ x = 1 \][/tex]
Step 5: Verify the solution [tex]\( x = 1 \)[/tex] in the original equation.
[tex]\[ f(1) = \sqrt{5(1) - 1} - 2 \][/tex]
[tex]\[ \quad \ = \sqrt{5 - 1} - 2 \][/tex]
[tex]\[ \quad \ = \sqrt{4} - 2 \][/tex]
[tex]\[ \quad \ = 2 - 2 \][/tex]
[tex]\[ \quad \ = 0 \][/tex]
Since substituting [tex]\( x = 1 \)[/tex] back into the original function gives [tex]\( f(1) = 0 \)[/tex], we confirm that [tex]\( x = 1 \)[/tex] is indeed a zero of the function.
Therefore, the zero of the function [tex]\( f(x) = \sqrt{5x - 1} - 2 \)[/tex] is:
[tex]\[ x = 1 \][/tex]
Step 1: Set the function equal to zero.
To find the zeroes of the function, we set [tex]\( f(x) = 0 \)[/tex]:
[tex]\[ \sqrt{5x - 1} - 2 = 0 \][/tex]
Step 2: Solve for [tex]\( \sqrt{5x - 1} \)[/tex].
[tex]\[ \sqrt{5x - 1} = 2 \][/tex]
Step 3: Square both sides to eliminate the square root.
[tex]\[ (\sqrt{5x - 1})^2 = 2^2 \][/tex]
[tex]\[ 5x - 1 = 4 \][/tex]
Step 4: Solve for [tex]\( x \)[/tex].
Add 1 to both sides:
[tex]\[ 5x = 5 \][/tex]
Divide both sides by 5:
[tex]\[ x = 1 \][/tex]
Step 5: Verify the solution [tex]\( x = 1 \)[/tex] in the original equation.
[tex]\[ f(1) = \sqrt{5(1) - 1} - 2 \][/tex]
[tex]\[ \quad \ = \sqrt{5 - 1} - 2 \][/tex]
[tex]\[ \quad \ = \sqrt{4} - 2 \][/tex]
[tex]\[ \quad \ = 2 - 2 \][/tex]
[tex]\[ \quad \ = 0 \][/tex]
Since substituting [tex]\( x = 1 \)[/tex] back into the original function gives [tex]\( f(1) = 0 \)[/tex], we confirm that [tex]\( x = 1 \)[/tex] is indeed a zero of the function.
Therefore, the zero of the function [tex]\( f(x) = \sqrt{5x - 1} - 2 \)[/tex] is:
[tex]\[ x = 1 \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.